Sodium Formate as Low Temperature Phase Change Material in Cold Storage Insulation Box - Chen Wenpu; Zhang Xuelai; Huang Yan; Ren Yinglei; Ding Jinhong (Zhileng xuebao)
The cold storage material of HCOONa?2H2O 21%+water 79% which have appropriate phase change temperature, large latent heat, large thermal conductivity and good stability was studied in this paper. Cold storage insulation boxes with two kinds of insulation layers have been produced, one is pure polyurethane foam (PU) and the other is vacuum insulation panel and polyurethane foam (VIP-PU). Cold storage agents were frozen in the low temperature refrigerator and then were put into the cold storage insulation boxes. Different quality of cold storage agents and different freezing temperature were studied. The results showed that the cold storage effect of the VIP-PU box is two times of the PU box. When the coolant quality is 15 kg and the freezing temperature is ﹣60 ℃, the VIP-PU cold storage box could maintain the temperature at ﹣10 ℃ for 13 hours, which has the optimal cold storage effect.